ANALYSIS OF THE QUALITY OF SYNCHRONOUS AND ASYNCHRONOUS DISTANCE LEARNING IN UIPA AND DETERMINATION OF PROSPECTS FOR ITS OPTIMIZATION - Ryabov , O. (Problems of Engineer-Pedagogical Education, 2023)
The relevance of the article is to reveal the technology of ensuring the quality of distance education based on a step-by-step evaluation of the developed materials, to identify the criteria for the completeness of the mandatory and additional components of the course studied remotely on the website of the HEI. Such an examination is called structural and functional and consists of three parts: mandatory group 1; mandatory group 2; additional group 3. Mandatory groups include general information; course annotations, work program, information about the teacher, scores for assignments, tasks for practical and independent work of students, module control issues, methodological instructions for practical and independent tasks. An additional group includes lecture texts, presentations, glossary, etc. Completeness criteria are developed for each department, as each department has its own characteristics and specifics of educational disciplines. The article provides tables of completeness criteria for the Department of Foreign Languages and for all other departments. The second type of expertise that is proposed is the support expertise. For the Department of Foreign Languages, it consists of two mandatory groups. The first group includes: enrollment of students, timely checking of assignments, correctness of hyperlinks, student activity, etc. The second group includes the availability of comments in case of not using the maximum score for an assignment, feedback through surveys, etc. For other departments, the content of peer review is slightly different, namely: two main groups covering the correctness of the date of assignments, the availability of a list of groups with student option numbers, timeliness of assignment checking, and the activity of the teacher and students; the third additional group takes into account the activity of the teacher's pedagogical activity and the activity of teamwork in the DL. The constant use of peer review during the semester and periodic assessment of the completeness of the course content studied by students allows for ongoing adjustment of the content and methods of mastering the disciplines, which improves the quality of distance learning. The article discusses the procedure for certification of an e-learning course and the procedure for establishing and operating a certification commission. The analysis of distance learning at UIPA allowed the author to identify the main reserves that can be used to improve the quality of online learning. The conclusions highlight some problematic issues that should be addressed by teachers, students and the administration of the higher education institution. The conclusion is made that it is necessary to carry out a number of organizational, control, motivational measures within the HEI to optimize the content and control in the process of using distance education. For the prospect of further research, further development of the content of distance courses, the mechanism of their use and control to improve the quality of distance learning is determined.